2013
DOI: 10.1007/s11999-012-2618-7
|View full text |Cite
|
Sign up to set email alerts
|

Femoral Lateral Bowing and Varus Condylar Orientation Are Prevalent and Affect Axial Alignment of TKA in Koreans

Abstract: Background Coronal alignment is considered key to the function and longevity of a TKA. However, most studies do not consider femoral and tibial anatomical features such as lateral femoral bowing and the effects of these features and subsequent alignment on function after TKA are unclear. Questions/purposes We therefore determined (1) the prevalence of lateral femoral bowing, varus femoral condylar orientation, and severe tibia plateau inclination in female Koreans undergoing TKA; (2) whether postoperative alig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
121
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 98 publications
(126 citation statements)
references
References 37 publications
(91 reference statements)
4
121
1
Order By: Relevance
“…Furthermore, if Asian patients have certain demographic and anatomical characteristics known to affect clinical outcomes, special strategies to accom modate the unique nature of Asian patients may be required for preoperative patient counseling, prosthesis design, surgical technique, and postoperative rehabilitation. At the same time, considering the wide variances reported even within the same ethnicity group [16,18,25], treating Asian patients undergoing TKA similarly to patients from the West may render better outcomes in function and longevity, because the Western patient population is generally a diverse group, and treatment has evolved to best accommodate this diversity.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, if Asian patients have certain demographic and anatomical characteristics known to affect clinical outcomes, special strategies to accom modate the unique nature of Asian patients may be required for preoperative patient counseling, prosthesis design, surgical technique, and postoperative rehabilitation. At the same time, considering the wide variances reported even within the same ethnicity group [16,18,25], treating Asian patients undergoing TKA similarly to patients from the West may render better outcomes in function and longevity, because the Western patient population is generally a diverse group, and treatment has evolved to best accommodate this diversity.…”
mentioning
confidence: 99%
“…TK Kim: Several previous studies reported that Asian patients seeking TKA for their advanced osteoarthritic knees present with different anatomical characteristics and deformity patterns, for example, more severe varus deformity and flexion contracture with yet well-preserved knee flexion [3,16]. To what degree should the same surgical principles, namely, creation of neutral limb alignment and balanced gaps, be preserved?…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(2) Decide what modifications should be made in postoperative rehabilitation protocols to accommodate the unexpected events during surgery. For example, vigorous medial ligament release, which is often required in TKA for Asian knees with severe varus deformity, sometimes end up with complete release of superficial MCL, subsequently causing medial instability [5,7]. This type of medial instability originating from complete release of superficial MCL, arguably can be treated by surgical repair without using constrained types of prostheses [9] or even bracing without additional surgical remedy [6].…”
Section: Unexpected Adverse Events During Surgery-guiding Principlesmentioning
confidence: 99%
“…Certain surgical techniques may be more applicable in Asia than in the West. For Asian patients with TKA, additional surgical steps are more frequently required to address severe coronal or torsional deformity, which left untreated, can result in unbalanced asymmetrical gaps [3][4][5][6]. While ''traditional medicine'' may be a fad in the West, the ''traditions'' come from the East, and those traditions run long and deep in some parts of Asia.…”
Section: Introductionmentioning
confidence: 99%